Causes of Business Process Reengineering Failure in the Kingdom of Bahrain and Saudi Arabia - Khadija Al-Omran; Dr. Jamal AlZayer; Mahmoud Arnout (International Journal of Engineering and Management Research, 2019)
Business Process Reengineering (BPR) has been one of the methodologies which aims at achieving a radical change that would drive the organization to new heights and assists it to harness its potential. Even though there are literature that marked lots of success stories in BPR projects, there are also other literature that cited a failure rate that reaches 70%. To investigate the reasons behind BPR project failure, secondary data from past literature relevant to our research provided a platform to devise a wide-ranging register of ninety one (91) potential contributors to BPR project failure. These factors were reproduced in a Likert type questionnaire to elicit the views of respondents and allow the researcher carry out causal analysis. The data collected in the empirical field research from Kingdom of Bahrain and Kingdom of Saudi Arabia which accounts for one hundred and ninety two (192) responses, it was diverse in terms of process, industry, managerial position, company size and others. The analysis showed that the improper reengineering of IS legacy systems, ineffective process redesign problems, IT investment & sourcing decision, training problems and ineffective use of consultants are the most significant contributors to a BPR project failure whereby these factors can collectively explain about 69.8% of the variation in the BPR project failure. IBM-SPSS software was used in the data analysis phase of this work.